Students Attitudes Toward the Use of Artificial Intelligence Tools in English Language Learning - Rosmayanti, Vivit (Universitas Muhammadiyah Mataram, 2024)
This research intends to assess the point of view of English Education students of Universitas Negeri Makassar regarding the application of Artificial intelligence (AI) resources in the skin of language learning. In this context, the research may engage AI tools Grammarly, ChatGPT, and others and analyze both the benefits and the challenges associated with these applications. The study adopted a convergent parallel design and collected qualitative and quantitative data from 100 respondents through surveys and interviews. The findings revealed that using AI tools increases learning efficiency (89%), enhances writing (82%), and boosts students’ self-efficacy toward completing academic work (75%). Nonetheless, difficulties such as excessive dependence on AI, lack of comprehension of the functionalities of the specified tools, to mention a few, and the problem of depending on the accuracy of responses generated by AI were also documented. In addition, the research brings attention to the potential of AI in language education while stressing the importance of integration to avoid dependence. It is recommended for educators to reinforce responsible use of AI, discourage misuse of AI, uphold academic honesty, and discourage autonomous use of AI. In the next strides, the study will require other attention in the areas of most interest when using AI tool inclusion measures better aimed at addressing the barriers identified impacting the use of language tools for students.